On-board implementation and experimental validation of collaborative transportation of loads with multiple UAVs - Bacelar, Tiago (2021)
This paper presents a methodology and the experimental validation for collaborative load transportation using two UAVs (Unmanned Aerial Vehicles). The state variables are estimated, based on measurements from motion sensors installed on-board. Control and estimation solutions were required to ensure the stability of the system, while guaranteeing null steady-state position and estimation errors. The vertical velocity is also estimated since there is no sensor on-board the UAVs capable of providing this measure directly. The relative position between the UAVs is estimated using only on-board sensors and images acquired by the UAV front camera. The controllers and estimators resort to linear and optimal control techniques, as the Linear Quadratic Regulators and Kalman filters. The proposed control system is validated both in simulation and experimentally, resorting to a commercially available quadrotor equipped with an Inertial Measurement Unit, an ultrasound height sensor, vertical and frontal cameras.